Multipotent Mesenchymal Stromal Cells in Rheumatoid Arthritis and Systemic Lupus Erythematosus; From a Leading Role in Pathogenesis to Potential Therapeutic Saviors? - El-Jawhari, Jehan J.; El-Sherbiny, Yasser; McGonagle, Dennis; Jones, Elena (Frontiers in Immunology, 2021)
The pathogenesis of the autoimmune rheumatological diseases including rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) is complex with the involvement of several immune cell populations spanning both innate and adaptive immunity including different T-lymphocyte subsets and monocyte/macrophage lineage cells. Despite therapeutic advances in RA and SLE, some patients have persistent and stubbornly refractory disease. Herein, we discuss stromal cells' dual role, including multipotent mesenchymal stromal cells (MSCs) also used to be known as mesenchymal stem cells as potential protagonists in RA and SLE pathology and as potential therapeutic vehicles. Joint MSCs from different niches may exhibit prominent pro-inflammatory effects in experimental RA models directly contributing to cartilage damage. These stromal cells may also be key regulators of the immune system in SLE. Despite these pro-inflammatory roles, MSCs may be immunomodulatory and have potential therapeutic value to modulate immune responses favorably in these autoimmune conditions. In this review, the complex role and interactions between MSCs and the haematopoietically derived immune system in RA and SLE are discussed. The harnessing of MSC immunomodulatory effects by contact-dependent and independent mechanisms, including MSC secretome and extracellular vesicles, is discussed in relation to RA and SLE considering the stromal immune microenvironment in the diseased joints. Data from translational studies employing MSC infusion therapy against inflammation in other settings are contextualized relative to the rheumatological setting. Although safety and proof of concept studies exist in RA and SLE that support experimental and laboratory data, robust phase 3 clinical trial data in therapy-resistant RA and SLE is still lacking.